2021
DOI: 10.1002/cm.21682
|View full text |Cite
|
Sign up to set email alerts
|

Myosin's powerstroke occurs prior to the release of phosphate from the active site

Abstract: Myosins are a family of motor proteins responsible for various forms of cellular motility, including muscle contraction and vesicular transport. The most fundamental aspect of myosin is its ability to transduce the chemical energy from the hydrolysis of ATP into mechanical work, in the form of force and/or motion. A key unanswered question of the transduction process is the timing of the force-generating powerstroke relative to the release of phosphate (P i ) from the active site. We examined the ability of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(49 citation statements)
references
References 68 publications
(202 reference statements)
5
43
0
Order By: Relevance
“…Single-molecule optical tweezers results 26,48 have favored a powerstroke-first model. The estimated time scale of powerstroke for cardiac myosin (1 ms 26 ) is independent of Pi concentration and faster than Pi release rate (ranging from a few ms to 60 ms 26,49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Single-molecule optical tweezers results 26,48 have favored a powerstroke-first model. The estimated time scale of powerstroke for cardiac myosin (1 ms 26 ) is independent of Pi concentration and faster than Pi release rate (ranging from a few ms to 60 ms 26,49 ).…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that the assays and analyses they employed had the ability to detect a change in myosin's powerstroke, Scott et al (2021) simulated data assuming either a powerstroke-first or a P i -release first model and confirmed that if myosin bound to actin and paused before generating a powerstroke it would have been evident in their observations. Therefore, they concluded that their findings strongly favor a model in which myosin's powerstroke precedes the release of P i from its active site.…”
Section: Testing the New Theory At The Single Molecule Levelmentioning
confidence: 99%
“…In a second independent test of this hypothesis, Scott et al (2021) determined the effect of increasing the P i concentration to 30 mM on the single molecule mechanics and kinetics using a wild-type myosin Va construct at 100 μM ATP. If P i -release gates the powerstroke, and therefore is released before the powerstroke, the elevated (P i ) should have reduced the amplitude of the powerstroke and/or slowed the rate the powerstroke.…”
Section: Testing the New Theory At The Single Molecule Levelmentioning
confidence: 99%
See 2 more Smart Citations